City of Ghosts - Heineman, Matthew (USA, 2017)
City of Ghosts follows the work of “Raqqa is Being Slaughtered Silently”, a Syrian citizen journalist group reporting war news and human rights abuses committed by ISIS in the city of Raqqa from 2014 till 2017. Providing unique access to events and locations, the film trails this dedicated group as they face the harsh realities of life undercover and risk their lives to record the horrors of occupation.
Keywords: Documentary films